Adenosquamous carcinoma of the ampulla of vater. Issue 2 (February 2015) - Dekate, Jyoti; Chetty, Runjan
Abstract Adenosquamous carcinoma of the ampulla of Vater is an uncommon malignant tumor comprising about 1% of ampullary carcinoma. It is characterised by a combination of two malignant components; one glandular and the other squamous. This histological variant is associated with an aggressive clinical outcome and dismal prognosis. There has been persistent uncertainty about its histogenesis and clinicopathological features Here, in this paper, we present a case report of ampullary adenosquamous carcinoma, addressing the provlem areas including the diagnostic criteria, its histogenesis and practical issues in the pathologic evaluation of this neoplasm.